Journalism in an Age of Terror - Lloyd, J (I.B.Tauris, 2016)
The threat of terrorism and the increasing power of terrorist groups have prompted a rapid growth of the security services and changes in legislation permitting collection of communications data. This provides journalism with acute dilemmas. The media claims responsibility for holding power to account, yet cannot know more than superficial details about the newly empowered secret services. This book is the first to analyse, in the aftermath of the Snowden/NSA revelations, relations between two key institutions in the modern state: the intelligence services and the news media. It provides the answers to crucial questions including: how can power be held to account if one of the greatest state powers is secret? How far have the Snowden/NSA revelations damaged the activities of the secret services? And have governments lost all trust from journalists and the public?